Preliminary Investigation of Bovine Whole Blood Xenotransfusion as a Therapeutic Modality for the Treatment of Anemia in Goats - Smith, Joe S.; Viall, Austin K.; Breuer, Ryan M.; Walton, Rebecca A.; Plummer, Paul J.; Griffith, Ronald W.; Kreuder, Amanda J. (Frontiers in Veterinary Science, 2021)
Anemia requiring whole blood transfusion for appropriate treatment is a common clinical presentation of caprine patients to veterinary practitioners, however, identifying suitable blood donors in goat herds can be challenging. In other veterinary species, the practice of xenotransfusion, where blood from one species is transfused to another, is used in emergency settings. Due to their ability to donate large volumes of whole blood, cattle could be an ideal source for xenotransfusion of goats. In this study two healthy goats were transfused with bovine whole blood. The goats were then monitored for adverse effects and the presence of bovine erythrocytes post-xenotransfusion. Afterwards, 15 caprine-bovine combinations were evaluated for compatibility via cross-matching. Both goats tolerated xenotransfusion, although transient reactions were observed. Of the 15 cross-match combinations, 11 of the major cross matches were compatible, and all minor cross matches were compatible. While future work is necessary to refine this technique, xenotransfusion of goats with cattle blood may be a therapeutic modality for the treatment of caprine anemia.